2015
DOI: 10.18632/oncotarget.6443
|View full text |Cite
|
Sign up to set email alerts
|

Serum cyclin-dependent kinase 9 is a potential biomarker of atherosclerotic inflammation

Abstract: Atherosclerotic coronary artery disease (CAD) is one of the most prevalent diseases worldwide. Atherosclerosis was considered to be the single most important contributor to CAD. In this study, a distinct serum protein expression pattern in CAD patients was demonstrated by proteomic analysis with two-dimensional gel electrophoresis coupled with mass spectrometry. In particular, CDK9 was found to be highly elevated in serum, monocytes and artery plaque samples of CAD patients. Furthermore, there was high infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Previous studies have demonstrated that CDK9 played a crucial role in cardiomyocyte proliferation and atherosclerosis. 16 , 19 Therefore, we assessed the possible interaction between PEBP1P2 and CDK9 by bioinformatics analyses. Using RNA-protein interaction prediction (RPISeq), the potential PEBP1P2-binding protein was predicted, and CDK9 was shown to interact with PEBP1P2 by the random forest (RF) classifier (=0.80) and support vector machine (SVM) classifier (=0.58) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that CDK9 played a crucial role in cardiomyocyte proliferation and atherosclerosis. 16 , 19 Therefore, we assessed the possible interaction between PEBP1P2 and CDK9 by bioinformatics analyses. Using RNA-protein interaction prediction (RPISeq), the potential PEBP1P2-binding protein was predicted, and CDK9 was shown to interact with PEBP1P2 by the random forest (RF) classifier (=0.80) and support vector machine (SVM) classifier (=0.58) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 , 17 In addition to its crucial role in cancer cell metabolism and cardiomyocyte proliferation, recent studies have shown that it may also play an important role in CVDs, as it was detected to be upregulated in artery plaque, serum, and monocyte samples of coronary heart disease (CHD) patients. 16 , 18 , 19 However, the regulatory function and mechanism of CDK9 in VSMC phenotypic conversion are mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, the 28S ribosomal protein S36 (mitochondrial, P82909), has not yet been assigned to any particular condition, but AVS, as reported in the previous study [6]. To name one last example, the E3 ubiquitin-protein ligase complex Ankyrin repeat and SOCS box protein 7 (Q9H672) is yet to be associated to a pathological setting and was found exclusively up-regulated in sera of CAD patients [24]. These and other examples of potential markers (octagonal orange nodes) for AVS or CAD are summarized in Fig.…”
Section: Integration Of the Outputs From Bioinformatics Analysismentioning
confidence: 77%
“…Since then, Flavopiridol has been considered as a golden standard for development and evaluation of new CDK9 inhibitors [238] [239,240]. Flavopiridol is currently undergoing a clinical trial as a treatment for acute myeloid leukemia (AML) [241], but it is also effective in arthritis and atherosclerotic plaque formation [242,243]. Because of the high potential of CDK9 inhibitors as therapeutic agents for various diseases including HIV/AIDS and cancer, many new CDK9 inhibitors have been developed ( Table 2).…”
Section: Suppressing P-tefb Activitymentioning
confidence: 99%